Energy transfer in interaction of a cold atmospheric pressure plasma jet with substrates. (8th April 2021) - Hansen, Luka; Goldberg, Benjamin M; Feng, David; Miles, Richard B; Kersten, Holger; Reuter, Stephan
Abstract: The energy flux of a nanosecond pulsed cold atmospheric pressure (CAP) plasma jet in contact with a substrate surface was measured to improve the understanding of the correlation between energy flux, flow dynamics and applied electrical power. The flow pattern properties of the CAP jet were imaged using Rayleigh scattering showing a transition from laminar to turbulent flow at Reynolds number of 700, significantly smaller than the conventional critical Reynolds number of 2040. The energy flux to the surface was determined using a passive thermal probe as a substrate dummy. As expected, the energy flux decreases with increasing distance to the nozzle. Measurements of the floating potential of the probe revealed a strong positive charging (up to 165 V) attributed to ion flux originating mainly from Penning ionization by helium metastables. Negative biasing of the probe doubled the energy flux and showed a significantly increased ion contribution up to a nozzle distance of 6 mm to the surface. For positive biasing an increased contribution of electrons and negative ions was only found at 3 mm distance. The relevance of particle transport to the surface is shown by switching from laminar to turbulent flow resulting in a decreased energy flux. Furthermore, a linear correlation of energy flux and input power was found.